2017
DOI: 10.1038/s41467-017-00769-0
|View full text |Cite
|
Sign up to set email alerts
|

Mef2C restrains microglial inflammatory response and is lost in brain ageing in an IFN-I-dependent manner

Abstract: During ageing, microglia acquire a phenotype that may negatively affect brain function. Here we show that ageing microglial phenotype is largely imposed by interferon type I (IFN-I) chronically present in aged brain milieu. Overexpression of IFN-β in the CNS of adult wild-type mice, but not of mice lacking IFN-I receptor on their microglia, induces an ageing-like transcriptional microglial signature, and impairs cognitive performance. Furthermore, we demonstrate that age-related IFN-I milieu downregulates micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
184
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(208 citation statements)
references
References 71 publications
24
184
0
Order By: Relevance
“…In addition, increased cerebral expression is also a characteristic of physiological ageing in humans and mice (Baruch et al, 2014). In mouse studies, this was associated with activation and a proinflammatory phenotype of CNS-resident microglia (Deczkowska et al, 2017), and in vivo blockade of IFN-I signaling in aged mice improved cognitive function (Baruch et al, 2014). While these studies demonstrate that increased levels of IFN-I may be present in a wide range of neurological conditions and mediate either beneficial or detrimental effects, much work is still required to clarify their roles in specific diseases and conditions.…”
mentioning
confidence: 99%
“…In addition, increased cerebral expression is also a characteristic of physiological ageing in humans and mice (Baruch et al, 2014). In mouse studies, this was associated with activation and a proinflammatory phenotype of CNS-resident microglia (Deczkowska et al, 2017), and in vivo blockade of IFN-I signaling in aged mice improved cognitive function (Baruch et al, 2014). While these studies demonstrate that increased levels of IFN-I may be present in a wide range of neurological conditions and mediate either beneficial or detrimental effects, much work is still required to clarify their roles in specific diseases and conditions.…”
mentioning
confidence: 99%
“…IFN‐I signaling is upregulated in aged human microglia (Olah et al, ), as well as microglia from both physiological and Ercc1‐accelerated aging mouse models (Grabert et al, ; Holtman et al, ). Importantly, further profiling of the aging microglia phenotype by Deczkowska et al () showed that the microglial transcriptome of aged mice is largely defined by a response to IFN‐I, most likely a response to IFN‐β which is chronically produced at elevated levels by the choroid plexus in both aged humans and mice (Baruch et al, ). Intracerebroventricular administration of anti‐IFNAR1 neutralizing antibodies to the CSF of aged mice results in microglial transcriptomic changes inversely related to those found in the aging phenotype (Deczkowska et al, ).…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroimentioning
confidence: 99%
“…Similar to aged microglia, AAV-IFNβ microglia are highly reactive, have an increased number of cellular processes, and upregulate the expression of genes regulated by IFN-I (Deczkowska et al, 2017), as well as genes that are linked to cognitive decline in aging (Smith et al, 2015). The specific deletion of IFN-I signaling in microglia rescues AAV-IFNβ mice from IFN-β-driven synaptic loss and cognitive decline (Deczkowska et al, 2017). Importantly, chronic IFN-I signaling in aged mice and AAV-IFNβ mice also reduces the microglial expression of myocyte enhancer factor, Mef2C, a transcription factor which regulates the unique microglial chromatin landscape (Lavin et al, 2014) and restricts the response of microglia to inflammatory stimuli (Deczkowska et al, 2017).…”
Section: Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ex vivo microglia isolated from adult mice show greater secretion of both IL‐6 and TNFα (Njie et al, ). Gene ontology analysis on transcriptomic data from young and aged mice reveals that these changes are largely IFN‐dependant (Deczkowska et al, ). These changes are accompanied by morphological alterations, most notably with observations of hypertrophy (Conde and Streit, ).…”
Section: Microglia Transcriptomic Changes In Admentioning
confidence: 99%